DYNAMICS OF THE LEVEL OF SENSITIZATION TO RAGWEED AND WORMWOOD IN SAMARA IN 2012–2017 - N. N. Zhukova; M. V. Manzhos; L. R. Khabibulina; E. V. Aseeva; T. V. Moiseeva; M. V. Zhdanova; I. I. Rodin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The true prevalence of pollinosis in general and of weed susceptibility to pollen in particular (mainly wormwood and ragweed) in Russia and worldwide has not been studied enough. The ragweed is a quarantine weed, which is a native species in Russia. Wormwood is a large genus of herbaceous plants, in Russia the most common bitter and common wormwood. The aim of the study was to study the level of sensitization to ragweed pollen and wormwood in Samara region for 5 years. In the city of Samara revealed the growth of sensitization to ragweed pollen and wormwood from 2012 to 2017, which is consistent with the data on the leading role of ragweed pollen and wormwood as a risk factor for the development of pollinose in the region. Taking into account the data on ragweed distribution in the region is three separate, to avoid cross-reactions between allergens of different types of ragweed and wormwood, and to identify the truth of sensitization in these patients should be conducted component allergy diagnostics.